Why buying Halal labelled food? Understanding the spending behavior of non-Muslim consumers in Malaysia - Phuah, Kit Teng; Wan Jusoh, Wan Jamaliah (2017)
Food plays an important role in the social, cultural and religious life of many communities. Food which is consumed by Muslims must meet the Islamic dietary code and this code is called halal. Halal is derived from the Arabic word meaning lawful or permitted. The demand for Halal products is increasing especially in Muslim country. However, the research on Halal labeled food consumption on non-Muslim market segment has been largely ignored. Objective: To investigate the reasons non-Muslim consumer purchase Halal labeled food and their spending behavior towards Halal labeled food given all the advantages of such products. Results: The results for multiple regressions shows that consumers’ spending behavior is influence by the non-Muslim consumers’ income level, their understanding towards Halal concept, degree of intention and degree of concern towards animal welfare and fair trade. Conclusion: Future study is needed to examine how non-Muslim consumers with different levels of motivation and halal knowledge and understanding respond to the halal labelled food. It is also interesting in examine how the consumers’ needs and wants can be satisfied through developed marketing strategies by marketers.